Determination of pitch angles and wind speeds ranges to improve wind turbine performance when using blade tip plates. (September 2019) - Ansari, M.; Nobari, M.R.H.; Amani, E.
Abstract: In this article a wind turbine performance enhancement is studied numerically using two type of tip plates. A three dimensional finite volume code is developed to simulate the wind turbine flow field periodically at different wind speeds and pitch angles. The well-known Menter's Shear Stress Transport ( k ω − S S T ) turbulence modelling is incorporated into the code to investigate the turbulent flow field that occurs in wind turbines. Here we show that using tip plates for wind turbines performance improvement can only occur if the turbine blade pitch angle is set at the maximum output power based on the given wind speed. Otherwise, using the tip plates play negative role and reduce the wind turbine output power. This physical effect is related to the wind turbine working condition at which both the blade span-wise flow as well as the tip blade trailing vortices stay at their minimum amount. Highlights: Highlight: Detailed study of the effect of adding tip plate to the wind turbine blade on the wind turbine performance. Pointing out the span-wise flow importance on the wind turbine performance. Exploring the range of pitch angles and wind speeds at which adding tip plates can improve the wind turbine performance.